Camuflagem química de Attacobius Lavape (Araneae: Corinnidae) parasita social de Solenopsis saevissima (Hymenoptera: Myrmicinae) - (:unkn) unknown (Universidade Estadual de Goiás, 2019)
Several chemical compounds are used in the communication of the ants and the hydrocarbons present in the cuticle (HCC) make up a group involved in the recognition of the nestmates. This process helps defend the colony against invaders as well, but some animals, known as myrmecophils, have the ability to break this barrier in many ways, including mimicking such chemical signals for their own benefit. Attacobius lavape, a species of spider recently described, was found in the municipality of Morrinhos, Goiás State, Brazil, feeding on eggs, larvae and pupae inside colonies of the fire ant Solenopsis saevissima and we hypothesized that A. lavape uses this strategy to avoid being recognized as an enemy. Thus, we identified by gas chromatography the HCC of spiders and young and adult workers collected in the municipality of Morrinhos. The Permanova analysis detected a difference between the chemical composition of the samples (young ant, adult ant and spiders) (F = 6.64, gl = 2, R2 = 0.42, p < 0.001), and by post hoc to-peer, only the young ants did not differ from the spiders. The results demonstrate chemical mimicry as a form of integration of A. lavape to mymecophily with S. saevissima to predate eggs, larvae and pupae.
Chemical camouflage of Attacobius lavape (Araneae: Corinnidae) social parasite of Solenopsis saevissima (Hymenoptera: Myrmicinae)
Keywords: Hidrocarbonetos cuticulares; Mirmecofilia; Aranha; Cuticular hydrocarbons; Mymembrane; Spider; CIENCIAS BIOLOGICAS